OPTIMIZATION OF THE COMPANY'S COMMUNICATION STRATEGY BASED ON THE COMBINATION OF PUSH AND PULL STRATEGIES - HAVLOVSKA, Nataliia; ZAHARCHUK, Nataliia; RUDNICHENKO, Yevhenii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
Communication strategy is an integral part of strategic management, as it determines how the organization interacts with internal and external stakeholders (consumers, partners, investors, government agencies, media, etc.). It helps to form a positive image of the company, strengthen its reputation and maintain effective relations with target audiences. Communication strategy should be understood as a comprehensive approach to managing the interaction of the enterprise with the internal and external environment, which includes the integration of business goals, objectives and policies of the enterprise into specific actions in the field of communications. It is noted that the communication strategy is a component of the operational strategies of the organization, as it directly affects the implementation of marketing, management and business processes, using an integrated approach to external and internal communications. The process of its formation is presented. The article examines the key communication models used in marketing strategies to form effective interaction with consumers. In particular, the classic models AIDA, AIMDA, ACCA, 4A, 4P, DIBABA and DAGMAR are considered, their characteristic features, mechanisms of influence on the target audience and possibilities of adaptation to modern conditions of digital marketing. The results of the study demonstrate that the choice of a communication model depends on marketing objectives, type of product and expected results of interaction with consumers. The article considers communication strategies for product promotion – Push Strategy (push strategy) and Pull Strategy (consumer attraction strategy). Their features, advantages and feasibility of use depending on market conditions, goals of the enterprise and stage of the product life cycle are studied. It was determined that the Push strategy is effective for stimulating intermediaries and distributors to actively promote products, which is especially important for mature products or products that are in a decline stage. At the same time, the Pull strategy is aimed at creating demand among end consumers, which is key when introducing new products to the market.
Keywords: strategy; communication models; communication strategy; Push Strategy; Pull Strategy